Are you Sleeping? Pilot Comparison of Self-Reported and Objective Measures of Sleep Quality and Duration in an Inpatient Alcoholism Treatment Program - Alyssa T. Brooks; Michael C. Krumlauf; Barbara P. Whiting; Rosa J. Clark; Gwenyth R. Wallen (SAGE Publishing, 2012)
Sleep disturbances are common among alcohol-dependent individuals and can increase risk of relapse. The current study compares subjective and objective measures of sleep quality and duration and describes the prevalence of baseline sleep disturbances in an inpatient population of alcoholics undergoing their first week of detoxification. At baseline, the PSQI revealed that 79% of participants were above the cutoff score (≥5) for clinically meaningful sleep disturbances (mean = 12.57, SD = 4.38). Actigraphy results revealed that average sleep efficiency was 75.89%. Sleep efficiency scores were significantly correlated with self-reported sleep efficiency ( P = 0.04, r = 0.47). Sleep duration measured by the actigraphy watches was not significantly correlated with self-reported sleep duration ( P = 0.65, r = 0.10). Ongoing assessment of sleep disturbances may be a valuable tool for informing the development of customized sleep interventions in a similar inpatient alcohol treatment sample.